Initial seven coefficient estimates for a subclass of bi-starlike functions - Janani, T.; Yalçın, S. (Ukrains’kyi Matematychnyi Zhurnal, 2021)
UDC 517.5In the present article, a subclass of bi-starlike functions is studied and initial seven Taylor–Maclaurin coefficient estimates $|a_{2}|, |a_{3}|, … , |a_{7}|$ for functions in the subclass of the function class $ Σ $ are obtained for the first time in the literature. Few new or known consequences of the results are also pointed out.